Changing theory
1 online resource
Keywords: "This book is an original, systematic, and radical attempt at decolonizing critical theory. Drawing on linguistic concepts from sixteen languages from Asia, Africa, the Arab world, and South America, the essays in the volume explore the entailments of words while discussing their conceptual implications for the humanities and the social sciences everywhere. The essays engage in the work of thinking through words to generate a conceptual vocabulary that will allow for a global conversation on social theory that will be necessarily multilingual. With essays by scholars, across generations, and from a variety of disciplines - history, anthropology, and philosophy to literature and political theory - this book will be essential reading for scholars, researchers and students of critical theory and the social sciences"--